The effect of exclusive breastfeeding on the growth of infants aged 7-12 months in the balla parang health center work area - Muldaniyah, Muldaniyah (Innovative Approaches in Health Science Journal, 2024)
Background: The growth phase is an important period for a baby's life. One of the most important factors in the growth phase is nutritional needs. Nutrition is needed since the baby is in the womb until birth. Nutrition When the baby is born, it is obtained from giving exclusive breastfeeding to the growth of babies aged 7-12 months in the Balla Parang Health Center work area. Method: This study uses a quantitative research type with a retrospective research design. The sampling technique uses purposive sampling. The number of samples is 30 respondents. Results: The results of the study obtained a p value = 0.0004 (p <0.05) this identifies that there is a relationship between giving exclusive breastfeeding to the growth of babies aged 7-12 months in the Balla Parang Health Center work area, Makassar. Conclusion: Exclusive breastfeeding affects the growth of babies aged <6 months and mothers should avoid giving complementary foods/formula milk to meet the baby's nutrition so that growth can be achieved optimally